Efektivitas Program Kegiatan Layanan Anak di Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Rahmadi, Ardian; Marlini, Marlini (Scinary, 2025)
This study aims to evaluate the effectiveness of the children’s service program at the Archives and Library Office of West Sumatra Province. The research employed a descriptive quantitative approach using an assessment instrument covering various service indicators. The findings indicate that, overall, the children’s service program falls within the “fair” category, with an average score of 3.01. The facility and environment indicator shows that the service space is comfortable and safe but has yet to fully support an engaging and enjoyable learning atmosphere. The reading material collection is relatively diverse in terms of genres and age levels, but still lacks sufficient educational multimedia resources. In terms of programs and activities, initiatives such as storytelling sessions, reading competitions, and creative workshops have been implemented, though not consistently or systematically. Service delivery and staff competence were also rated as fair, with library staff considered friendly and communicative, although further improvement is needed in understanding child development needs. Access to information and parental involvement is relatively good, particularly through direct communication with library staff, yet the use of social media as an information platform remains underutilized. Lastly, the program’s target accuracy indicator shows that services are fairly aligned with children’s interests and needs, though continuous evaluation and program adjustments are necessary to ensure greater relevance and impact. These findings highlight the need to strengthen various aspects to enhance the overall quality of children’s services.